PERJANJIAN KERJASAMA PADA PERUSAHAAN DAERAH AIR MINUM KOTA KENDARI - Muhammad Rifqy; Maruf Akib; Wahyudi Umar (Halu Oleo University, 2024)
Public-private partnerships (PPPs) are an increasingly popular strategy in the provision of public services, such as clean water, infrastructure, and health. This article aims to analyze the factors that influence the success of such partnerships and their social and economic impacts on communities. This research method combines normative and empirical approaches to determine the cooperation agreement of the Regional Drinking Water Company (PDAM) in Kendari City. The results of the study show that in this context, political commitment, transparency, selection of the right partner, and continuous evaluation are considered key factors. In addition, the positive impacts of PPPs include increased access and quality of services, while the challenges faced such as inequality in access to services require special attention. Therefore, wise management is needed to ensure that this partnership provides fair benefits to all levels of society.